PHYTOCONSTITUENTS, PHARMACOLOGICAL ACTIVITY, AND MEDICINAL USE OF LEPIDIUM SATIVUM LINN.: A REVIEW - CHETNA BAREGAMA,; ANJU GOYAL, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Herbal medicines are in nice demand within the developed additionally as developing countries for primary aid due to their wide biological and medicative activities, higher safety margins, and lesser prices. Lepidium sativum Linn. (Brassicaceae) is annual herb regionally referred to as halon in India, however, usually referred to as garden cress. L. sativum is a fast growing edible plant. Seeds, roots, and leaves of garden cress have economic importance; however, the crop is especially cultivated for seeds. It is a therapeutic vital herb in India. L. sativum has various pharmacological actions such as antibacterial activity, antifungal activity, antioxidant activity, cytotoxic activity, diuretic activity, hepatoprotective activity, hypoglycemic activity, antiosteoporotic activity, antiasthmatic activity, anti-carcinogenic effect, cardiotonic activity, smooth and skeletal muscles contraction activity, fracture healing property, chemoprotective effects, and hemagglutinating activity. It is used for menstrual cycle regulation, gastrointestinal problems such as diarrhea and constipation and to increase milk production. It is also reported to exhibit antirheumatic activity. It is also used as an immunity booster and brain intellect enhancer agent as traditional medicine. So that this review reveal that L. sativum is a source of medicinally active compounds and have a variety of pharmacological effects. These studies will be helpful to create focus toward L. sativum and may be useful in developing new formulations with more therapeutic and to provide a direction for advance research.